Trends and performances of the algal biofuel: a bibliometric approach - Gao, Conghao; Xin, Huaijia; Yang, Shu; Li, Zhuo; Liu, Shulin; Xu, Bin; Zhang, Tianyang; Dutta, Susmita; Tang, Yulin (Journal of Environmental Engineering and Landscape Management, 2022)
The paper systematically presents a survey of the literature on algal biofuel by a bibliometric assessment. Based on 10,201 articles extracted from the Science Citation Index Expanded database during 1980–2019, a knowledge-generating system about algal biofuel has been established through analysis of publication performance, social networks, citations analysis and keywords analysis. Annual publication output in algal biofuel research has rapidly increased, particularly over the past decade. “Bioresource Technology” is the most outstanding journal when all analysis indices have been taken into account. The USA ranks 1st with 2,151 publications and has a high supremacy in international research collaborations. Through the analysis of keywords, the research trends of algae biofuel in algae selection, cultivation, harvesting, extraction, conversion and bioproducts are reviewed. The future of algal biofuel is quite promising, however, for its commercial production, several technical challenges like large-scale algal biomass production, cheap harvesting technology, etc. have to be met a-priori.